2020
DOI: 10.1007/978-3-658-28128-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Translanguaging in Early Childhood Education in Luxembourg: From Practice to Pedagogy

Abstract: An inclusive translanguaging pedagogy aims to promote learning and participation by drawing on the learners' entire semiotic repertoire. The focus of this chapter are the translanguaging practices of four early years practitioners in Luxembourg. We analyse the deployment of their linguistic repertoire, their reasons for translanguaging, and the ways in which their practices contributed to inclusion and participation. We found that the practices comprised using linguistic resources dynamically, translating, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Had we only used one of the methodological tools (RQ2), we would not have identified these ambivalent and paradoxical findings (RQ1), which in fact show a realistic picture of the majority of preschool teachers in early multilingual education in Luxembourg (e.g. Kirsch & Aleksić, 2018;Kirsch & Seele, 2020). Other recent studies have reported ambivalent attitudes and difficulties in understanding and implementing translanguaging pedagogy (e.g.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Had we only used one of the methodological tools (RQ2), we would not have identified these ambivalent and paradoxical findings (RQ1), which in fact show a realistic picture of the majority of preschool teachers in early multilingual education in Luxembourg (e.g. Kirsch & Aleksić, 2018;Kirsch & Seele, 2020). Other recent studies have reported ambivalent attitudes and difficulties in understanding and implementing translanguaging pedagogy (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…Finally, in Luxembourg, Kirsch and Seele (2020) cautioned that despite teachers' positive attitudes towards children's home languages and translanguaging, some teachers in their study, while translating and using home languages, were not aware of their students' real linguistic needs and did not reflect on how to include them in the classroom. This was corroborated by our recent study in which, during the home language activity where children were asked to choose the flags of their home countries, teachers insisted that Portuguese and Serbian children choose Portuguese and Serbian flags despite children's obvious refusal and desire to choose the Luxembourgish flag so that they feel included in the class (Aleksić & García, 2022).…”
Section: Translanguaging Pedagogy and The Focus On Translanguaging St...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, translation has the potential to develop inclusive practices which value and legitimise all languages and cultures in the classroom as resources for learning. It encourages participation and supports students' socio-emotional development (Kirsch & Seele 2020). However, studies have also alerted us to tensions in and potentially exclusionary implications of flexible language use in educational settings.…”
Section: Translation As Communicative Resource In Educational Spacesmentioning
confidence: 99%